IMPLEMENTASI PROGRAM BAZNAS KOTA BEKASI DALAM UPAYA PENINGKATAN PENDIDIKAN MASYARAKAT DHUAFA - Aiz, Muhammad; Juniyati, Famelia; Nabil, Nabil (Almarhalah: Jurnal Pendidikan Islam, 2022)
This study aims to describe that The National Zakat Board -BAZNAS as an Amil Zakat Institution, one of its duties and functions is for community empowerment. The issue of delinquent fee in educational institutions is a main concerns in this research. “Bekasi Cerdas”; as educational program from BAZNAS is helping the poor and needy so they would be able to continue their education. The research method used in this study is qualitative. The data in this study was obtained from 28 respondens of Baznas beneficiaries. The results can be concluded that there is a require for synergy between Baznas and the government in overcome educational problems in an effort to empower community in particular the poor.